1995
DOI: 10.1128/jb.177.13.3736-3742.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of csh203::Tn917lac, a mutation in Bacillus subtilis that makes the sporulation sigma factor sigma-H essential for normal vegetative growth

Abstract: spo0H encodes a sigma factor, sigma-H, of RNA polymerase that is required for sporulation in Bacillus subtilis. Null mutations in spo0H block the initiation of sporulation but have no obvious effect on vegetative growth. We have characterized an insertion mutation, csh203::Tn917lac, that makes spo0H essential for normal growth. In otherwise wild-type cells, the csh203::Tn917lac insertion mutation has no obvious effect on cell growth, viability, or sporulation. However, in combination with a mutation in spo0H, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…It seems that there is an unknown autogenous control of the level of oA in B. subtilis. One possibility is that this control is carried out by transcription from promoters other than P1P2 on the sigA operon, as reported for the csh203 : : Tn9171ac mutant of B. subtilis in which the minor o factor oH becomes essential for the expression of oA and for vegetative growth (Hicks & Grossman, 1995). The induction of oA synthesis in B. subtilis DBlOO5(pCX2F5) at 49 "C was unexpected since the mutant 8 lost most of its activity at the elevated temperature (Figs 4,5 ) and no such induction was observable in B. subtilis DB1005 under heat stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that there is an unknown autogenous control of the level of oA in B. subtilis. One possibility is that this control is carried out by transcription from promoters other than P1P2 on the sigA operon, as reported for the csh203 : : Tn9171ac mutant of B. subtilis in which the minor o factor oH becomes essential for the expression of oA and for vegetative growth (Hicks & Grossman, 1995). The induction of oA synthesis in B. subtilis DBlOO5(pCX2F5) at 49 "C was unexpected since the mutant 8 lost most of its activity at the elevated temperature (Figs 4,5 ) and no such induction was observable in B. subtilis DB1005 under heat stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The csh203::Tn977/ac transposon insertion was found to be in the first gene, orf23, of the rpoD operon ( Fig. 1) and caused an increase in expression of genes controlled by sigma-H (Hicks and Grossman, 1995). subfilis.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we had identified several transposon-generated lacZfusions to genes that are controlled by sigma-H; csh genes. One insertion mutation, csh203::Tn917/ac, caused spoOHto be essential for normal vegetative growth (Jaacks eta/., 1989;Hicks and Grossman, 1995). That is, a csh203::Tn917/ac spoOH double-mutant strain had a growth defect while each single-mutant strain grew normally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of experiments have shown that the increase in H activity as measured by transcription of H -dependent genes does not match the accumulation of the H protein, implying the existence of posttranslational controls (8,16,17,21,23,45,50). Furthermore, evidence has been presented that external pH (8) and the activity of the tricarboxylic acid cycle (26) affect H activity and that H protein levels are affected by a Lontype protease during the onset of sporulation and during stress responses (30).…”
mentioning
confidence: 99%